Navigating the depths: A comprehensive narrative review on depression in people with epilepsy - Norah A. Alkhaldi (Heliyon)
Epilepsy presents a significant global health challenge, impacting millions worldwide. Alarmingly, over half of individuals living with epilepsy (PWE) also face concurrent medical conditions, with psychiatric complications, particularly depression, standing out as prevalent issues. The relationship between epilepsy and depression is complex and bidirectional, with approximately a quarter of adults with epilepsy receiving a diagnosis of depression. This complexity underscores the challenges in diagnosing depression in epilepsy patients, hindered by overlapping symptoms and distinct manifestations of depression in this population. Our review highlights that the use of most antidepressant pharmacotherapies does not increase the risk of seizure occurrences. On the contrary, compelling evidence suggests that such treatments may even decrease seizure frequency, offering hope for patients. In addition to pharmacology, non-pharmacological interventions are emerging as vital alternatives, enriching the therapeutic landscape. However, despite these promising avenues, a significant gap in our understanding persists, characterized by a lack of comprehensive, prospective research. Our review rigorously explores the latest pathophysiological insights linking depression and epilepsy while critically evaluating contemporary treatment paradigms for individuals grappling with these comorbid conditions. By focusing on the most current developments, this review aims to equip clinicians with cutting-edge knowledge, fostering a more nuanced and effective approach to managing the intricate interplay between epilepsy and comorbid depression.